2022
DOI: 10.7717/peerj.13486
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of seafood mislabeling

Abstract: A substantial portion of seafood is mislabeled, causing significant impacts to human health, the environment, the economy, and society. Despite the large scientific literature documenting seafood mislabeling the public’s awareness of seafood mislabeling is unknown. We conducted an online survey to assess the public’s awareness and perceptions of seafood mislabeling. Of the 1,216 respondents, 38% had never heard of seafood mislabeling and 49% were only ‘vaguely familiar’ with it. After being provided the defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…were either unaware or only vaguely familiar with the practice of seafood mislabelling prior to taking the survey (Ryburn et al, 2022).…”
Section: Con Sumer Choice and S Hark Sus Tainab Ilit Ymentioning
confidence: 99%
See 2 more Smart Citations
“…were either unaware or only vaguely familiar with the practice of seafood mislabelling prior to taking the survey (Ryburn et al, 2022).…”
Section: Con Sumer Choice and S Hark Sus Tainab Ilit Ymentioning
confidence: 99%
“…Mislabelling of seafood products can take several forms, such as fraudulent reporting of product identity, provenance or production system (e.g. wild‐caught vs. farmed‐raised; Kroetz et al, 2020; Ryburn et al, 2022). For simplicity, we include poor or ambiguous labelling, where a single common name is used to designate a range of species, as a type of mislabelling even though it does not involve product substitution.…”
Section: Labelling Of Seafood Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study observed around 80% of hilsa has been mislabeled as chapila by fisherman and seller of different fish market. Similarly, the mislabeling of fish and many seafood items has been reported frequently in the local market of many countries of the world, causing deleterious impacts on human health, environment, the economy and the society (Munguia-Vega et al 2021;Ryburn et al 2022;Cundy et al 2023). Furthermore, the majority of exchanges recognized in our samples were, on average, fewer costly and apparently less wanted alternatives to jatka.…”
Section: Phylogenetic Analysis Using Neighbor-joining Treementioning
confidence: 99%
“…At the same time due to the complex and valuable supply chains of this commodity, there is a potential increase in fish mislabeling and/or fraud [ 3 ]. Fish mislabeling is defined as an inaccurate labeling of a specimen’s species name, weight and geographic origin [ 4 ]. Economic profit by the difference in price is the main criterion of intentional fraud by the substitution of expensive species for cheaper ones, while consumers are exposed to the risk of buying harmful products containing allergens [ 5 ] or endangered species are threatened since the substitute is exploited without reporting, thus undermining conservation efforts by supporting unsustainable or illegal fishing activities [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%